Efficient Access to 2,3-Dihydroquinazolin-4(1H)-ones by Environmentally Benign l-Proline Nitrate as Recyclable Catalyst - Bahekar, Sandeep P.; Dahake, Nityanand D.; Sarode, Prashant B.; Chandak, Hemant S. (Synlett, 2015)
An l-proline nitrate assisted protocol is described for the construction of 2,3-dihydroquinazolin-4(1H)-ones. The catalyst can be recovered easily and is reusable for at least six cycles without significant loss of catalytic efficiency.
Keywords: 2,3-dihydroquinazolin-4(1H)-one; l-proline nitrate; ionic liquid; cyclocondensation reaction